Copper Oxide/HKUST‐1 Composite Catalyst as Thermal Decomposition Modifier on Ammonium Perchlorate. Issue 3 (27th December 2021) - Nair, Savitha; Francis, Tony; Nair, C. P. Reghunadhan; Mathew, Suresh
Abstract: Metal‐organic framework and graphitic carbon nitride (g‐C3 N4 ) are structures of high specific surface area. The Cu 2+ incorporated classical metal‐organic frameworks (HKUST‐1) synthesized by the solvothermal method was used for the synthesis of ternary composite catalyst. When copper oxide was loaded into HKUST‐1/g‐C3 N4, the resulting composite system was found to be highly effective catalysts for the thermal decomposition of ammonium perchlorate (AP). The doped metal oxide in HKUST‐1/g‐C3 N4 functioned as a catalyst for the thermal decomposition of ammonium perchlorate. The composite catalyst was characterized by X‐ray diffraction (XRD). The effect of composite catalyst on the thermal decomposition of AP was studied using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results indicated that the composite system showed excellent catalytic activity towards the thermal decomposition of AP. The high‐temperature decomposition of AP decreased by 72 °C on using HKUST‐1 based ternary composite catalyst. The large surface area of HKUST‐1, g‐C3 N4, and copper oxide nanoparticles play key roles in reducing the decomposition temperature. This was further confirmed by the kinetic analysis of the sample using the Kissinger‐Akahira‐Sunose method. Abstract :